A bimetallic (Ni/Co) metal–organic framework with excellent oxidase-like activity for colorimetric sensing of ascorbic acid. Issue 14 (24th March 2023) - Wan, Jing; Zou, Jian-Mei; Zhou, Shu-Jing; Pan, Feng-Lan; Hua, Fei; Zhang, Yu-Lan; Nie, Jin-Fang; Zhang, Yun
Abstract : A novel colorimetric platform was constructed based on the excellent intrinsic oxidase-like activity of a bimetallic Ni/Co-MOF catalyst, which was synthesized by using a simultaneous precipitation and acid etching method with ZIF-67 as the template. Abstract : A novel nanozyme of bimetallic (Ni/Co) metal–organic framework (Ni/Co-MOF) was synthesized using a simultaneous precipitation and acid etching method with a zeolitic imidazolate framework ZIF-67 as the template. The as-synthesized Ni/Co-MOF catalyst presented a three-dimensional hollow nanocage structure and exhibited excellent intrinsic oxidase-like activity. It was demonstrated that Ni/Co-MOF could directly catalyze the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to produce a blue product (oxidized TMB, oxTMB) in the absence of H2 O2 . The mechanisms and kinetics of this nanozyme activity were investigated, and it was determined that the catalytic activity of Ni/Co-MOF was closely related to temperature and solution pH. Owing to its strong reducibility, ascorbic acid (AA) could reduce oxTMB, and the blue color of the reaction mixture faded over time. Therefore, a novel colorimetric platform was constructed to detect AA based on the oxidase-like activity of Ni/Co-MOF. Under optimal conditions, the absorbance of ox-TMB at 652 nm decreased linearly over the 0.015–50 μM AA range with a detection limit of 0.004 μM.